TREND ANALYSIS OF THERMAL COMFORT INDICES IN THREE DIFFERENT CLIMATES OF IRAN OVER 15 YEARS - Mehdi, Asghari; Gholamabbas , Fallah; Somayeh , Farhang Dehghan (Advanced Journal of Environmental Sciences (AJES), 2023)
this study aimed to assess the trend of thermal comfort indices in the outdoor environment of three different climates in Iran over a 15-year period. The meteorological data required to estimate the thermal comfort indices were obtained from the Iran Meteorological Organization for the period between 2000 and 2014. Three thermal comfort indices, including the humidex, temperature-humidity, and effective temperature, were utilized for estimation. The results revealed that Arak, representing the cold and semi-arid climate, experienced warm conditions in June, July, and August. Sari, representing the humid subtropical climate, had warm conditions in June, July, and September, while August was very hot. Bandar Abbas, representing the hot and arid climate, had sultry conditions in May, June, and September, while July and August had extremely hot conditions. These findings suggest the need for precise and innovative policies and programs to prevent and reduce the risks associated with climate change and global warming. The trend analysis of air temperature and thermal indices over the years can serve as a guide for future planning and adopting preventive or control measures to protect people from thermal stress hazards in outdoor environments.